Theoretical foundations of the study of children’s fiction - Sarbayeva , Dilnoza (The Lingua Spectrum, 2025)
Children’s literature, as an independent artistic phenomenon with its own language and stylistic features, is analyzed in depth in terms of linguistic, philological, didactic, aesthetic and pragmatic aspects. This article is based on the following theoretical directions: Children’s literature as an object of linguistic and philological analysis, Didactic and aesthetic tasks of children’s literature, Fundamentals of pragmatic analysis of texts. Language and style play an important role in the analysis of children’s literature. Texts written for children should usually be simple, clear and figurative. Because it may be difficult for a young reader who is just learning children’s language to understand complex sentences. Therefore, short and concise sentences, frequently repeated words, animated images (personification), dialogues and a game style are widely used in children’s literature. These methods allow the child to better understand the text and participate in it. In addition, children’s literature serves to form socio-spiritual values. Therefore, children’s literature is seen not only as a source of artistic pleasure, but also as a source of moral education. Especially, children’s literature, which reflects national values, traditions and historical events, educates the younger generation in the spirit of respect for the motherland, national heritage and culture.